Mushroom Diversity of Amrite Community Forest, Kapilvastu, Nepal - Prasad, Dhruv; Pokhrel, Bhojraj (Himalayan Biodiversity, 2017)
A total of 38 wild mushroom specimens were collected for the period of 3 months (from June to September, 2016) from Amrite community forest of Bhalwad, Banganga municipality. Out of 38 species collected, 34 species were identified up to generic level belonging to 16 families. The most dominant family was Coprinaceae belonging to 5 species followed by Amanitaceae consisting of 4 species. 80% of the Tharu people were found to use mushroom as food, 12.5% as medicine and 7.5% of Tharu people don’t have any idea of food and medicinal value. On the other hand, 57.5% of the non-Tharu community in the study area use mushroom as food, 7.5 % use as medicine and 35% of non-Tharu community do not use mushroom as food and medicine.